Population Differences in the Genetic Polymorphism of CYP2B6 May Impact on the Pharmacology of MMT - Nasir, Mohamad; Nurfadhlina, Musa; Sean, Tan (KARGER, 2015)
Objective: Introduced by the German as a synthetic opioid analgesic, methadone is used world-wide as a substitution treatment for opioid dependence. It is a chiral compound and its pharmacology is complex. This can further be complicated by population differences in the genetic polymorphisms of enzymes metabolizing the drug and preferential metabolism of specific isomers. Administered as a chiral mixture, its active S-form is preferentially metabolized by the polymorphic CYP2B6, with the CYP2B6*6 allele [SNPs 785A>G (rs2279343) and 516G>T (rs3745274)] associated with slow metabolism.